Financial Distress vs Financial Health vs Financial Sustainability: Manakah yang Mencerminkan Pertumbuhan Ekonomi di Indonesia Saat Ini? - Kusumawati, Annisa Fitriana (Jurnal Akuntansi dan Pajak, 2024)
The urgency of this research came when the Covid-19 pandemic broke out in Indonesia. The Covid pandemic not only attacked human health, but also significantly impacted the economy. In the year Covid-19 emerged, economic growth in Indonesia fell by -2.07% in 2020. The decline in economic growth was due to the gap between public debt and state revenues, resulting in a fiscal deficit. Various policies have been implemented to increase economic growth and close the fiscal gap, such as the national economic recovery program, circular economic empowerment, and green economy penetration. Which programs are considered to be able to increase economic growth in the financial health corridor or furthermore the program is a renewable step to achieve financial sustainability. This study tries to answer the current conditions in Indonesia, namely is Indonesia still in distress? Or has Indonesia slowly recovered? Or has Indonesia moved towards economic sustainability? To answer these research questions, researchers used the Central Java Regency/City Government Financial Report for 2020-2022 as a tool and population in this study. The research sample was selected using purposive sampling. The data source was obtained through the bpk.go.id website. For data analysis, researchers used SPSS 26 software. The results of the research conducted by the study indicate that Indonesia's current economic growth is reflected in financial health conditions. In addition, through various national economic recovery programs, Indonesia has been able to overcome financial distress conditions. However, economic growth in Indonesia unfortunately has not projected a state of financial sustainability.